Evolução crustal, geocronologia e geologia isotópica do Orógeno Araçuaí-Ribeira (AROS) no sul do Espírito Santo - Raíssa Santiago Mendes (2022)
The Araçuaí-Ribeira orogenic system (AROS) constitutes a part of the Mantiqueira Province developed during the formation of Western Gondwana in the Late Neoproterozoic. Similar to several orogenic belts formed during the PanAfrican/Brazilian event, the AROS is characterized by intra-oceanic and continental Neoproterozoic magmatic arcs. The Ribeira orogen comprises the Serra da Prata and Rio Negro intra-oceanic Tonian-Cryogenian transitional arcs and both the Ribeira and Araçuaí orogens are characterized by the Ediacaran Rio Doce continental arc, suggesting a complex geodynamic evolution. The Caxixe batholith, defined in this work, is a multi-intrusion composite batholith widely distributed in the southern Espírito Santo state, with approximately 110 km in length and width ranging between 12 and 21 km. It is composed mainly of granodioritic to granitic biotite-orthogneisses, with calcalkaline geochemical affinity, metaluminous to slightly peraluminous, magnesian, type I, with slight enrichment in light rare earth elements (LREE) in relation to heavy ones (HREE), positive to slightly negative anomalies of Eu and negative anomalies of NbTa. Most of the Caxixe batholith and adjacent plutons have ages between 580 and 608 Ma, with differentiated εHf(t), εNd(t) and 87Sr/86Sr indicating important crustal contamination. These characteristics are typical of rocks of the Ediacaran Rio Doce arc. However, Tonian rocks (840-860 Ma) occur locally in this batholith as roof pendants and megaxenoliths. These present typically juvenile εHf(t), εNd(t) and 87Sr/86Sr ratios, plotting on the depleted mantle curve. These rocks represent fragments of juvenile island arcs, probably the northern end of the Serra da Prata magmatic arc. Completing the magmatic edifice of the Caxixe batholith and vicinities, there are also syn-collisional garnet-bearing leucogranites at ca. 575 Ma, syn- to tardicollisional mafic intrusions at ca. 560 Ma and post-collisional leucogranite intrusions of about 503 Ma. The peraluminous paragneisses and hornblende-biotite gneisses that occur as country rocks to these plutons present geochemistry similar to magmatic arc basins and U-Pb age spectra of detrital zircon with main peaks between 600 and 800 Ma, indicating derivation from sedimentary and volcaniclastic rocks related to the magmatic arc systems. Thus, the 360 Ma of magmatic and sedimentary activity recorded in the Caxixe batholith and its surroundings in the southern Espírito Santo state are of enormous relevance for the understanding of the tectonic evolution of Western Gondwana, recording the pre-, syn- and post-collisional stages of theorogenic building of the AROS. We propose a model of tectonic evolution with the docking of the Tonian magmatic arc rocks in the passive continental margin of the Angola paleocontinent, followed by the subduction polarity inversion and development of the Rio Doce continental arc in the Ediacaran by melting of the continental margin and docked terranes. This was followed by collision between the São Francisco and Angola paleocontinents and orogenic collapse in the Cambrian.